HUBUNGAN MEROKOK DENGAN CALCULUS INDEX PADA REMAJA DI BR. DUKUH PESIRAHAN DENPASAR SELATAN TAHUN 2015 - Ni Ketut Ratmini; Ni Nyoman Dewi Supariani (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Smoking has become a habit that is very common and widespread in the community. Efforts to improve the oral health is an effort being made to change the behavior of a person, group of people or community, so as to have a habit of healthy living behavior in the field of oral health. In smokers tend to form more plaque and tartar that can lead to gingivitis (bleeding gums, swollen).This study aims to determine the relationship of smoking with the calculus index in teenagers in Banjar Dukuh Pesirahan Pedungan Denpasar Selatan 2015. The research method is cross cectional, the research data is secondary data from Yudhistira study research about illustration of OHIS in teenager smokers in Br. Dukuh Pesirahan Denpasar Selatan 2014, using Spearman analyses test . Results showed there is significant association between smoking and calculus index.